Site-specific nutrient management for rice using soil properties to adjust phosphorus and potassium supply from compound NPK fertilizer - Girsang, Setia Sari; Castillo, Rowena L.; Syam, Mahyuddin; Zaini, Zulkifli; Kartaatmadja, Sunendar; Suyamto; Dela Torre, Judith Carla; Pabuayon, Irish Lorraine B.; Limpiada, Romalene A.; Waluyo; Helmi; Samijan; et al. (Elsevier, 2025)
"Context or problem: Compound fertilizers containing nitrogen (N), phosphorus (P), and potassium (K) are often applied to rice (Oryza sativa L.) in Asia, but the fixed P:K ratio of these fertilizers can restrict the adjustment of P and K rates to match crop needs. Objective or research question: We hypothesized that site-specific nutrient management (SSNM) using a locally available NPK fertilizer could increase rice yield and then that soil properties could be used to better adjust nutrient inputs to match crop needs. Methods: Yield responses to added N, P, and K in on-farm nutrient omission plot technique (NOPT) trials across Indonesia were used to develop an SSNM practice, which was evaluated relative to farmer’s fertilizer practice (FFP) in 528 on-farm trials with lowland rice. Relationships of soil properties with yield responses were then examined across 38 additional trials on diverse soils. Results: An SSNM practice with one NPK fertilizer supplying all P and K increased yield by 0.4 Mg ha−1 and increased gross return above fertilizer cost by 173 USD ha−1 compared to FFP. The SSNM practice used less N and P but slightly more K than FFP. Median relative yields — defined as the ratio of yield in a nutrient omission plot and yield in a full-fertilizer plot — were 0.75 without added N, 0.94 without added P, and 0.94 without added K for 252 NOPT trials. Based on NOPT trials, the SSNM practice could be improved by applying more K at some locations because the P:K ratio of 0.52 (P2O5:K2O = 1) for the NPK fertilizer was higher than the estimated optimum to meet crop needs. Higher K requirement was associated with soil pH < 5.5, soil K saturation < 1.8 %, and soil base saturation < 40 %. Conclusions: Farmer’s P use for rice can often be reduced with an upper limit for the P rate set to match the net removal of P by the crop. An NPK fertilizer with P:K ratio = 0.44–0.52 would meet P and K requirements at many locations, and a mid-season topdressing of additional K could be targeted to locations requiring more K. Higher K use could target areas with soil pH < 5.5, which could be approximated from soil maps and verified with soil test kits. Implications or significance: The examination of associations between crop response to a nutrient and soil properties, other than soil nutrient status, merits use elsewhere to identify soil characteristics helpful in fine-tuning SSNM."